Pengaruh Model Pembelajaran Snowball Throwing Berbantuan Praktikum Sederhana terhadap Motivasi Berprestasi Siswa pada Materi Koloid di SMA Negeri 16 Samarinda - Tiara Panduwinata; Muh. Amir; Yuli Hartati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the Snowball Throwing learning model assisted by simple experiments on students’ achievement motivation in colloid material. The independent variable in this study is the Snowball Throwing learning model assisted by simple experiments, while the dependent variable is students’ achievement motivation. The type of research used is a quasi-experiment with a post-test only control group design. The population of the study consisted of all 38 students of class XI MIA at SMA Negeri 16 Samarinda, all of whom were taken as samples using a saturated sampling technique. The research instruments were an achievement motivation questionnaire and an observation sheet. Data were analyzed using normality tests, homogeneity tests, and t-tests at a significance level of 0.05. The results showed that the average score of students’ achievement motivation in the experimental class was higher, at 83.68%, compared to the control class, which was 75.53%. Therefore, it can be concluded that the application of the Snowball Throwing learning model assisted by simple experiments has a positive and significant effect on students’ achievement motivation in colloid material at SMA Negeri 16 Samarinda.